Inovasi Instrumen Penilaian Non Tes Maharah Kalam dengan Pembuatan Video Hiwar Kreatif di MAN 4 Banyuwangi - Sabrina, Banat; R Umi Baroroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this scientific study is to provide a non-test assessment tool by creating a creative dialogue video on the topic of shopping. This research was conducted using a qualitative approach with data collection. The primary data comes from eleventhgrade students at the Islamic State Senior High School 4 Banyuwangi, while the secondary data is sourced from relevant documents related to the research. The analyses show the results of using the assessment tool that evaluates speaking skills, where students are classified into several categories including fluency, pronounciation, grammar and activity. The results indicate that students in the